On the Skitovich-Darmois Theorem for a-Adic Solenoids - Mazur, I.P. (Журнал математической физики, анализа, геометрии, 2013)
By the Skitovich-Darmois theorem, the Gaussian distribution on the real line is characterized by the independence of two linear forms of n independent random variables. The theorem is known to fail for a compact connected Abelian group even in the case when n = 2. In the paper, it is proved that a weak analogue of the Skitovich-Darmois theorem holds for some a-adic solenoids if we consider three independent linear forms of three random variables. По теореме Скитовича-Дармуа гауссовские распределения на вещественной прямой характеризуются независимостью двух линейных форм от n независимых случайных величин. Хорошо известно, что эта теорема перестает быть справедливой для компактной связной абелевой группы даже в случае, когда n = 2. В этой статье мы доказываем, что имеет место слабый аналог теоремы Скитовича-Дармуа для некоторых a-адических соленоидов, если рассматривать три линейные формы от трех случайных величин.